POLA ASUH ANAK DARI ORANG TUA BERCERAI In Lubuk Layang Kecamatan Rao Selatan Kabupaten Pasaman - Yanti, Fitri; Fachrina, Fachrina; Elfemi, Nilda (Pendidikan Sosiologi, 2014)
This research is describe about how to keep child from broken home in Nagari Lubuk Layang Kecamatan Rao Selatan Kabupaten Pasaman, this problem give effect to their child because a mother not only to keep the child, but have character a father for her child. The research problem is how to keep a broken home child in that place. The goals of research is describe keep child from broken home and problems to attend child from broken home. In this research used qualitative approach.Researcher used questioning strategy to get data. The researcher have technique choose informant with purposive sampling, from this technique researcher choose who is informant research can use. Pola Asuh Anak dari Orang Tua Bercerai used theory is Structural Fungsional by Talcott Parsons about society is a sociality, if one of system get problem, so will give effect to other system. The result of research show parent used permissive method, where is parent give freedom to child, because have broken parent. Other parent found used democratic to keep their child with give clearly rules for act and character a child. The conclusion in this research is attend permissive form and democratic to their children from broen parent because a parent have less times to stay in home with their children.